ANTICORRUPTION POLICY IN HIGHER EDUCATION AND NEW ACADEMIC ETHICS - Marina N. Makarova; Roman V. Vakhrushev (Высшее образование в России)
The article considers the global and Russian experience in creating anticorruption policy and academic ethics in higher education institutions, analyzes different forms of corruption and academic misconduct in the West and in Russia, factors of corruption and dishonest behavior in academic environment. The main directions of anticorruption policy in higher education include adoption of ethical codes and other ways of shaping “culture of integrity” in contemporary higher education. The modified academic code accentuates the issues of academic honesty and ethics, includes sanctions and punishments for its infringement, formulates concrete and intelligible standards and regulations.